Tinjauan Literatur Penerapan Akuntansi Pesantren Pada Pesantren Di Indonesia - Febriyanti, Safira; Mardian, Sepky (IAIN Kudus, 2023)
This study aims to look at productivity and distribution, the most prolific authors, methodologies that are often used, trends in research topics, constraints in applying Islamic boarding school accounting standards and future research directions published on Google Scholar in 2013-2022. The type of data used is secondary data in the form of research on the application of Islamic boarding schools accounting. The method used is descriptive quantitative with bibliometric analysis and Systematic Literature Review (SLR). The results of the research show that 2021 is the most productive year, scientific articles and theses are the most types of publications with the same level of productivity, and the most productive publisher and affiliation is UIN Maulana Malik Ibrahim. Lestari, Tri Utami became the most productive writer by publishing 2 scientific articles publications. The methodology that is often used is the qualitative method. Meanwhile, the research topic that has been researched the most is regarding the observation of financial reports based on Islamic boarding school accounting guidelines which state that the majority of Islamic boarding schools have not implemented Islamic boarding school accounting presentation standards. The obstacle faced is the lack of understanding and training.